Game Disinfectman sebagai Edukasi Penggunaan Disinfektan untuk Mencegah Penularan COVID-19 - Muhammad Haris Berliansyah; Mitra Istiar Wardhana; Arif Sutrisno (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: The COVID-19 virus, which was announced by the WHO as a global pandemic, made the government and the public begin to implement health protocols, including disinfection using special chemical liquids intended for inanimate objects. However, there are some misunderstandings about the use of disinfectant liquids in the human body that can endanger health. This is because the liquid used for disinfection contains chemicals, such as: diluted bleach (bleach solution), chlorine, ethanol, quaternary ammonium, and hydrogen peroxide which are harmful to the body. To eliminate these misunderstandings, the Disinfectman game was designed as an educational as well as entertainment media which is expected to eliminate misunderstandings about the use of disinfection fluids during the COVID-19 pandemic. The design method used in the development of this game is the ADDIE method which describes the systematic development of stages to get the results as needed. The stages in the ADDIE procedure are: analysis, design, development, implementation, evaluation. This disinfectman game was developed using the game developer application Unity Game Engine which uses the C# programming language and the Adobe Photoshop application to create 2D assets. To ensure the game can be played, a black box test was carried out as an effort to find errors or bugs in the game, this test showed that in general the game ran smoothly. This game is based on WEB GL HTML5 which is played online on the itch.io site. Keywords: disinfectant, games, COVID-19 Abstrak: Virus COVID-19 yang diumumkan WHO sebagai pandemi global membuat pemerintah dan masyarakat mulai menerapkan protokol kesehatan, diantaranya adalah disinfeksi menggunakan cairan kimia khusus yang diperuntukan untuk benda mati. Akan tetapi, terdapat beberapa kesalahpahaman penggunaan cairan disinfektan pada tubuh manusia yang dapat membahayakan kesehatan. Hal ini dikarenakan cairan yang digunakan untuk disinfektan mengandung bahan kimia, seperti: diluted bleach (larutan pemutih), klorin, etanol, ammonium kuarterner, serta hidrogen peroksida yang berbahaya bagi tubuh. Untuk menghilangkan kesalahpahaman tersebut, dirancanglah game Disinfectman sebagai media edukasi sekaligus hiburan yang diharapkan dapat menghilangkan kesalahpahaman penggunaan cairan disinfeksi pada masa pandemi COVID-19. Metode perancangan yang digunakan dalam pengembangan game ini merupakan metode ADDIE yang menggambarkan sistematik pengembangan bertahap untuk mendapatkan hasil yang sesuai kebutuhan. Tahapan yang ada pada prosedur ADDIE, yaitu: analisis, desain, pengembangan, implementasi, evaluasi. Game disinfectman ini dikembangkan menggunakan aplikasi pengembang game Unity Game Engine yang menggunakan bahasa pemrograman C# dan aplikasi Adobe Photoshop dalam pembuatan aset 2D. Untuk memastikan game dapat dimainkan, dilakukan uji coba black box sebagai upaya untuk menemukan error atau bug yang ada dalam game, uji coba ini menunjukan bahwa secara umum game berjalan lancar. Game ini berbasis WEB GL HTML5 yang dimainkan secara daring pada situs itch.io. Kata kunci: disinfektan, game, COVID-19